1 ³√40-√2/5+2√1/10= 2 1/2√32+√8/2-1/5√50= 3 42√1/6-(√50-2√32)√3=

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/07 06:45:03
1 ³√40-√2/5+2√1/10= 2 1/2√32+√8/2-1/5√50= 3 42√1/6-(√50-2√32)√3=
xP !m !ðF^Ckjl`[ppE=ec~!E1߭V 8i(#ꌤ8Q#Z9xy ŇY& Oc)y3U,K6w%J2r_6)tax9p,4ᚎ~#

1 ³√40-√2/5+2√1/10= 2 1/2√32+√8/2-1/5√50= 3 42√1/6-(√50-2√32)√3=
1 ³√40-√2/5+2√1/10= 2 1/2√32+√8/2-1/5√50= 3 42√1/6-(√50-2√32)√3=

1 ³√40-√2/5+2√1/10= 2 1/2√32+√8/2-1/5√50= 3 42√1/6-(√50-2√32)√3=
³√40-√2/5+2√1/10
= 2³√5-1/5√10+1/5√10
=2³√5
1/2√32+√8/2-1/5√50
= √8+√4-√2
=2√2+2-√2
=2+√2
42√1/6-(√50-2√32)√3
=7√6-√150+2√96
=7√6-5√6+8√6
=10√6